Call for Reforms in the NEET-UG Examination (National Eligibility cum Entrance Test - Undergraduate): Addressing Human Resources in Health for India, the World's Most Populous Country - Ranjan, Piyush; Kain, Sarthak; Kumar, Raman (Journal of family medicine and primary care, 2024)
ABSTRACT The National Eligibility cum Entrance Test for Undergraduate (NEET-UG) in India serves as a unified admission examination for undergraduate medical courses, aiming to standardize assessment across diverse educational backgrounds. Despite its goals, NEET-UG has faced criticism over fairness, excessive reliance on coaching, and its impact on students' holistic development. The article reviews the limitations of the current NEET-UG format and proposes reforms, emphasizing the need to align the syllabus more closely with medical requirements by reducing physics and chemistry content and prioritizing biology. It suggests restructuring NEET-UG into a two-step examination to improve differentiation among candidates and reduce malpractice. Introducing a computer-based format, expanding the question pool, and adding interdisciplinary topics relevant to healthcare, such as Psychology, Nutrition, Physical Education, Cell biology, Genetics, public health and sociology, are also recommended. Additionally, the paper compares NEET-UG with global medical entrance exams, noting that broader subject assessments and critical thinking skills could enhance candidate evaluation. The Indian medical education system is the largest in the world. Given its vast capacities, it is crucial to reform the selection process to ensure that human resources in health can effectively address the pressing public health needs of India, the world's most populated country. The proposed reforms aim to create a fairer, more comprehensive selection process that minimizes stress, encourages holistic education, and better meets medical education standards.